2015
DOI: 10.1002/acp.3148
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Individual Experiences Create Lifetime Periods: a Study of Autobiographical Memory in Persons with Spinal Cord Injury

Abstract: Previous research showed that transitional events causing catastrophic and long-lasting changes in group of people's lives (e.g., wars) create autobiographical periods. We investigated whether spinal cord injury (SCI), an involuntary and externally driven disruptive event at the individual level, would also act as a temporal landmark and spawn personal periods and whether these periods have comparable functions and temporal characteristics as those generated at the group level. Thirteen volunteers with SCI rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…If a diagnosis is perceived as a major life transition, age at diagnosis and its association with memory distributions may not be unique to schizophrenia. For example, a recent study demonstrated a reduction in memories following spinal cord injury [49], which restricts the range and nature of activities individuals can engage in. This suggests that any illness or disability that fundamentally changes life circumstances and/or identity can affect memory distributions.…”
Section: Discussionmentioning
confidence: 99%
“…If a diagnosis is perceived as a major life transition, age at diagnosis and its association with memory distributions may not be unique to schizophrenia. For example, a recent study demonstrated a reduction in memories following spinal cord injury [49], which restricts the range and nature of activities individuals can engage in. This suggests that any illness or disability that fundamentally changes life circumstances and/or identity can affect memory distributions.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of autobiographical memory research, a transition is an event or a set of events that causes a significant and enduring change in the fabric of life-in what people do, where they do it, and with whom (Brown, 2016;Brown, Hansen, Lee, Vanderveen, & Conrad, 2012). Several studies have documented the mnemonic importance of transitions (Bohn & Habermas, 2015;Brown, Schweickart, & Svob, 2016;Enz, Pillemer, & Johnson, 2016;Shi & Brown, 2016;Uzer & Brown, 2015;Zebian & Brown, 2014). In particular, they demonstrated that (a) transitions are often used as temporal landmarks when people attempt to date personal events, and (b) memorable personal events tend to Bpile up^around transitional events.…”
mentioning
confidence: 99%
“…A major life transition (i.e., the birth of a child) might usher in a new subjective stage in life, a new self (i.e., "being a TEMPORAL LANDMARKS 5 parent"). Indeed, major transitions have been shown to be linked to self-concept change (Cantor et al, 1987;Kling, Ryff, & Essex, 1997;Uzer & Brown, 2015). For example, student's description of themselves changed significantly as they transitioned from high school to university (Cantor et al, 1987).…”
Section: Memorymentioning
confidence: 99%
“…A person may feel more disconnected from their future self if this self is perceived as falling after a psychologically important event. Anticipated life transitions (e.g., becoming a parent or getting divorced) may be such salient landmarks that they chronically bisect the temporal landscape of one's life, similar to past life transitions (Cantor et al, 1987;Kling et al, 1997;Uzer & Brown, 2015). These events cause real life changes, so a sense of disconnection with selves on the other side of the landmark may be relatively unsurprising and based largely in fact.…”
Section: Temporal Landmarks In the Futurementioning
confidence: 99%
See 1 more Smart Citation